Anti-angiogenic effects of Qingdu granule on breast cancer through inhibiting NFAT signaling pathway. (10th August 2018) - Zhao, Xin; Liu, Jinyu; Feng, Lili; Ge, Shasha; Yang, Shijun; Chen, Chen; Li, Xiaoya; Peng, Lin; Mu, Yuxue; Wang, Yueqi; Gu, Daozhao; Guo, Yi; et al.
Abstract: Ethnopharmacological relevance: Qingdu granule (QDG), a traditional Chinese herbal prescription, had anti-tumor effect on breast cancer. However the underlying mechanism of QDG was unclear. The aim of this study: The present study aimed to investigate whether QDG could inhibit angiogenesis of breast cancer via acting on nuclear factor of activated T-cells (NFAT) signaling pathway. This was implicated in human umbilical vein endothelial cells (HUVECs) in vitro and breast cancer xenograft model in vivo. Materials and methods: The VEGF165 (15.58 ng/mL) induced human umbilical vein endothelial cells (HUVECs) were treated with serum samples containing tamoxifen (TAM), tacrolimus (FK506), or QDG with three dosages. The migration and canalization capacities of HUVECs were evaluated by transwell migration and tube formation assay. In 72 h-cultured HUVECs, The gene expression, protein amount, and nuclear translocation of NFATc3 were measured. The anti-tumor and anti-angiogenic effects of QDG in vivo were investigated in breast cancer xenograft model. The serum VEGF levels, microvessel density, and protein expressions (immunohistochemistry and western blot) of VEGF, VEGFR2 and NFATc3 were detected. Results: The results showed that, QDG significantly inhibited HUVEC migration and tube formation. It downregulated NFATc3 gene expression, decreased NFATc3 protein amount, and reduced the ratio of NFATc3 nuclear translocation in HUVECs. In breast cancer xenograft model, QDG treatment significantly suppressed tumor growth, inhibited VEGF release, and decreased microvessel density. QDG reduced protein expressions of VEGF, VEGFR2 and NFATc3. Conclusion: The results suggested that QDG showed anti-angiogenic effects of breast cancer both in vitro and in vivo. The mechanism might be partially associated with inhibiting NFAT signaling pathway. Graphical abstract: